2018
DOI: 10.1088/1755-1315/183/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Bio-organo-chemical fertilizers: a new prospecting technology for improving fertilizer use efficiency (FUE)

Abstract: Abstract. Fertilizer use efficiency (FUE) has been the focus of agriculture cultivation practices to meet economic and environmental challenges. Unfortunately, available technology for improving FUE is somewhat impotent as no significant breakthrough in fertilizer technology during the last several decades. However, by harnessing the most active components of chemical, organic, and biological sources to produce a multigroup fertilizer socalled bio-organo-chemical fertilizer, it is possible to develop a new te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Developed countries attach great importance to the use of organic fertilizers in agricultural production. Manure helps to supplement soil nutrients and reduce the use of chemical fertilizers 29,30 . In this experiment, combined with the staggered planting environment of farming and grazing in northern China, cow and sheep manure was selected as the base fertilizer in the four treatments.A large number of studies have shown that use of organic fertilizer can improve the physical and chemical properties of soil, and increase soil biological richness, enzyme activity, and nutrients, thus providing better conditions for growth of plant roots 31,32,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Developed countries attach great importance to the use of organic fertilizers in agricultural production. Manure helps to supplement soil nutrients and reduce the use of chemical fertilizers 29,30 . In this experiment, combined with the staggered planting environment of farming and grazing in northern China, cow and sheep manure was selected as the base fertilizer in the four treatments.A large number of studies have shown that use of organic fertilizer can improve the physical and chemical properties of soil, and increase soil biological richness, enzyme activity, and nutrients, thus providing better conditions for growth of plant roots 31,32,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Developed countries have attached great importance to the use of organic fertilizers in agricultural production. For example, manure helps to supplement soil nutrients and reduce the use of chemical fertilizers (Agegnehu et al, 2017;Goenadi et al, 2018). In this study, combined with the staggered planting environment of farming and grazing in northern China, cow and sheep manure fertilizer were selected as base fertilizer in the four fertilization treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In these plantations, the health and fertility of the soil play pivotal roles in determining the overall productivity of neem trees and the sustainability of the agricultural system. Soil degradation and nutrient depletion are pervasive issues in many neemgrowing regions and stem from factors such as overexploitation, land-use changes, and inadequate soil management practices (Goenadi et al, 2018;Liu et al, 2014). To address these challenges and ensure the long-term viability of neem plantations, it is imperative to adopt sound soil management strategies that revitalize the soil, enhance its health, and optimize nutrient availability (Youseff and Eissa, 2014).…”
Section: Introductionmentioning
confidence: 99%